2011
DOI: 10.1007/s00508-011-1579-2
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of child abuse amongst physicians – a descriptive study by a sample of rural Austria

Abstract: This study with a selected sample of physicians was conducted to assess their awareness and knowledge of child abuse. Two thirds (66.7%) of all participants confirmed contact with obviously abused children in the course of their professional life, whereas 87.3% did not report any prior education or training in that field. In relation to general practitioners, pediatricians had significantly more contacts with abused children (p = 0.021) and more prior education (p = 0.012). Results indicate that physicians in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…Conformingly, bruises/scarring and marks on the body were the most frequently mentioned symptoms, and responses pointing to symptoms of sexual abuse were virtually absent. These findings of health care providers having knowledge predominantly of physical abuse are consistent with those of CM studies in international literature [ 37 , 38 ]. A central challenge in the correct diagnosis of CM is that fact that most pediatric injuries globally (90%) are in fact unintentional and occur without malice [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Conformingly, bruises/scarring and marks on the body were the most frequently mentioned symptoms, and responses pointing to symptoms of sexual abuse were virtually absent. These findings of health care providers having knowledge predominantly of physical abuse are consistent with those of CM studies in international literature [ 37 , 38 ]. A central challenge in the correct diagnosis of CM is that fact that most pediatric injuries globally (90%) are in fact unintentional and occur without malice [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, future interventions to educate health care providers and increase knowledge should focus on individual-level risk factors for CM and encourage consideration of patient history and demographics in the assessment. Moreover, there is a need to better understand and treat negligence and emotional abuse as forms of CM, as well as provide long-term support to victims [ 26 , 37 , 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kraus and Jandl-Jager[18] found that the majority of physicians recognized the most common symptoms of child abuse. Alnasser et al [19] found that the Saudi medical students, pediatrics trainees, and pediatricians have good basic knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Our study states that 65.8% of the responders were not satisfied with their knowledge and 93% of them indicated they wanted some form of CME on abuse. It is reported that physicians in rural regions of Austria possessed basic knowledge on child abuse but were not aware of the referral system [ 24 ]. To improve diagnosis, reporting, strengthening the interaction with experts and to reduce fears in handling child abuse victim, better training is needed.…”
Section: Discussionmentioning
confidence: 99%